The Relationship Between Junk Food with the Incidence of Early Menarche Among Female Students Aged 9 – 12 Years Old at Al-Iman Private Elemantary School South Tangerang City - Widhawati, Riswahyuni; Ernawilis, Ernawilis; Purwanti, Heni (Universitas Ibn Khaldun Bogor, 2024)
Background : Early menarche is tihe first menstruation experienced by fertile woman under the age of 12 years. The condition of early menarche is because it gets more production of the hormone estrogen than other woman in general. One of the factors in occurrence of early menarche is caused by nutritional status as junk food as a food that is high in calories and fat but low in dietary fiber and if excessive consumption will stimulate the acceleration of reproductive organ maturity. Objective : To determine the relationship between junk food consumption with the incidence of early menarche among female students agen 9-12 years old at Al-Iman Private Elemantary School. Methods : This research is oobservational analytic with a cross sectional approach. The number of samples was 30 with the Quota Sampling technique. The instrument used was a questionnaire. Data were analyzed using the chi square test. Result : This study shows that there is a relationship between junk food consumption with the incidence of early menarche with the result of chi suare test with the alternative Fisher`s Exact Test obtained a value of p = 0,007 which means p < α = 0,05 and 95% CI 2,167 – 128,176. Conclusion : There is a relationship between junk food consumption with the incidence of early menarche among female students at Al-Iman Private Elemantary School. Suggestion: For further researchers to examine other variable that have not been studied with larger sample.